Impact of Training on Paddy Production Technology - M. K. Rathod; R. P. Mandve; G R. Tidke (Journal of Agricultural Extension Management, 2025)
This study was conducted in Bhandara district of Eastern Vidarbha Zone. Training programmes conducted by KVK, Bhandara on production technology of paddy were evaluated to assess the impact of these programmes. For this evaluation forty trainees were randomly interviewed and data collected for socio-economic and psychological characteristics as well as dimensions of training and developmental parameters. In case of independent variables, most of the respondents were found in the middle age group, with good educational status, possessed small land holding, were having medium type of land and temporary sources for protective irrigation. Most of the respondents were early adaptors and early majority of innovativeness. Scientific orientation and economic motivation of respondents were low. In case of intervening variables, majority of the respondents were having low level of knowledge, less favourable attitude, low to moderately motivated, less confident with low extent of adoption of paddy cultivation technology. Impact analysis reveals that level of knowledge, skills, attitude, motivation, confidence and adoption increased after the training programmes. Similarly, an increase in the developmental parameters viz. area under technology, production, productivity, family employment and annual income were recorded. Overall vertical impact of the training programmes on the farmers was about 30 per cent